The Crossroads between Infection and Bone Loss - Tiago Carvalho Oliveira (Microorganisms, 2020)
Bone homeostasis, based on a tight balance between bone formation and bone degradation, is affected by infection. On one hand, some invading pathogens are capable of directly colonizing the bone, leading to its destruction. On the other hand, immune mediators produced in response to infection may dysregulate the deposition of mineral matrix by osteoblasts and/or the resorption of bone by osteoclasts. Therefore, bone loss pathologies may develop in response to infection, and their detection and treatment are challenging. Possible biomarkers of impaired bone metabolism during chronic infection need to be identified to improve the diagnosis and management of infection-associated osteopenia. Further understanding of the impact of infections on bone metabolism is imperative for the early detection, prevention, and/or reversion of bone loss. Here, we review the mechanisms responsible for bone loss as a direct and/or indirect consequence of infection.